ABC regarding the general strikes in the socialist era in Spain, 1985-1994: beliefs, topics, class prejudice and journalistic information - Gálvez Biesca, Sergio (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This article proposes an unprecedented case study of the strategy and the editorial line of ABC, with regard to the general strikes called for by the main unions during the first socialist era in Spain (1982-1996). Within this contextual framework, an analysis is carried out of the pros and cons of using the media as a historical source, through which a context can be read, sequences can be located and, among other things, expressions of the society at a certain moment can become known. Finally, the text questions certain ideas-forces concerning the supposed rigorous and serious media character of ABC. As a social expression, it is full of ideological parameters, which can be read in the editorials, which reflect the interests of the Spanish economic elites.